Gender Brain Structural Differences and Interoception - Longarzo, Mariachiara; Mele, Giulia; Alfano, Vincenzo; Salvatore, Marco; Cavaliere, Carlo (Frontiers in Neuroscience, 2021)
Interoception, the ability to perceive inner body sensations, has been demonstrated to be different among genders, with a stronger female attention toward interoceptive information. No study correlated this capability with brain differences between males and females. This study aims to detect behavioral variances, and structural neuroimaging interoception correlates in a sample of healthy volunteers matched for age. 73 participants (37 females, mean age 43.5; 36 males, mean age 37.4) completed the Self-Awareness Questionnaire (SAQ) for interoceptive sensibility and underwent a structural MRI session. A t-test corrected for Bonferroni multiple comparisons was performed to compare brain morphological parameters (cortical thickness and parcels volume) in both groups. A multivariate analysis of variance was performed to assess the effect of gender on scores obtained on the SAQ. A moderation model through multiple linear regression analysis was performed between grey matter volumes or parcels, cortical thickness and the interoception score. Group analysis showed significant differences in morphometric brain data between males and females, both for cortical and subcortical volumes, but not for cortical thickness analyses. MANOVA underlined a significant difference in SAQ scores between males and females with higher values for the second ones. Moreover, a significant correlation between the interoception scores and grey matter volumes of the two groups have been detected, with a sharp prevalence for the female gender in the left insula with F1, F2, and SAQ interoception scores (R2 0.41, p <0.001). Our results demonstrated that in the female group, a stronger predisposition was found toward interoceptive sensations, and that multiple brain areas were correlated with interoceptive measure. These data sustain a female advantage in the attention toward this process and support the idea that in females, the interoception is a process more shared across several regions that participate in creating the sense of self.